Engaging Flipped-Classroom Model in An Indonesian EFL Grammar Instruction - Lina Marlina Heryana; Mobit Mobit; Iwan Ridwan (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Based on the researcher preliminary study, it was found that the flipped classroom models are used as learning models to assist students in facilitating grammar learning. This research aimed to investigate the process of using flipped classroom models in grammar teachings and to find out students' perceptions of grammar teaching using flipped classroom model. This research used qualitative approaches and design case study. Five students at high school participated as participants in the study. The researcher collected the data through observation and interview. The finding showed that the use of flipped classrooms could help students collaborate with each other between group members in formulating problem-solving provided by the teacher and can use class time to be more effective. In addition, flipped classrooms make the learning process easier to use, effective and useful. By using this learning model, most students can understand the material.